Psychosocial predictors of academic achievement in physical education among Indonesian university students: Testing the mediating role of mental toughness - Muhad Fatoni; Agam Akhmad Syaukani; Pungki Indarto; Imron Nugroho Saputro; Ismi Husniyah Musyfiroh (Physical Education and Sports: Studies and Research, 2025)
Background: Academic performance in this context is conceptualized holistically, encompassing the integration of cognitive, affective, psychomotor, and physical achievements. Grounded in Self-Determination Theory and Social Cognitive Theory, the study posits that physical activity interest and social skills serve as predictors of both mental toughness and academic outcomes. Objectives: This study examines the mediating role of mental toughness in the relationship between physical activity interest, social skills, and academic performance among university students enrolled in physical education programs. Methods: A quantitative approach was employed, involving the administration of structured questionnaires to 235 active students. Data were analyzed using Structural Equation Modeling with a Partial Least Squares approach to assess construct validity and the relationships among variables. Results: The results reveal that interest in physical activity and social skills has a significant influence on both mental toughness and academic performance. However, mental toughness did not serve as a substantial mediator within the proposed model. Conclusions: These findings underscore the critical direct roles of affective and social factors in predicting academic success in physical education contexts. Theoretically, this study clarifies the functional position of mental toughness, while practically, it promotes the development of instructional strategies that enhance intrinsic motivation and collaborative skills within physical education curricula.